Hepatosplenic Abscesses and Osteomyelitis of the Spine in an Immunocompetent Adult with Cat Scratch Disease - D. Knafl; F. Lötsch; H. Burgmann; G. Goliasch; W. Poeppl; M. Ramharter; F. Thalhammer; C. Schuster (Case Reports in Infectious Diseases)
We present an 18-year-old, immunocompetent Austrian military conscript with cervical lymphadenopathy, fever, back-pain, and persistent inflammation markers despite two weeks of antimicrobial therapy with ampicillin/sulbactam. All specific laboratory investigations for identification of a specific etiology, including blood cultures and autoantibodies, were inconspicuous. Abdominal computed tomography showed multiple hypodense hepatosplenic lesions and osteomyelitis of the thoracic and lumbar spine with base plate fracture. Based on the patient’s history, clinical presentation, and radiological findings, serology for cat scratch disease (CSD) was performed and high B. henselae specific IgM and IgG antibodies were detected. Due to its variety of clinical presentations, diagnosis of CSD is challenging, especially in the absence of a history of specific exposure. This case report shall remind the physician that cat scratch disease is a common disease, mainly presenting with fever and lymphadenopathy in young patients. Nevertheless CSD has many different and rare forms of presentations, including hepatosplenic lesions and bone involvement as shown in this case.